2018
DOI: 10.11158/saa.23.9.10
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Corynebacterium lactis isolated from Amblyomma testudinarium of Sus scrofa in Malaysia

Abstract: Ticks are vectors for a number of important human and animal pathogens. In this study, Corynebacterium lactis was isolated from Amblyomma testudinarium Koch tick sampled from wild boar in Malaysia. Imaging with transmission electron microscope and complete genome sequencing were performed for C. lactis which shared similar morphology to other Corynebacterium species and was susceptible to most of the commonly used antibiotics. The draft genome revealed a total length of 2,568,615 bp with G+C content of 64.3%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…We employed a non-selective bacterial culture method in this study, previously shown to enable isolation of rare and pathogenic bacteria species from tick specimens such as Corynebacterium lactis (Lim et al, 2018) and P. lautus (Loong et al, 2018a). Even though no bacterial growth was observed for some tick specimens, we suggest that it was not due to the limitation of the agar culture media but the method employed for bacterial isolation (Stewart, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…We employed a non-selective bacterial culture method in this study, previously shown to enable isolation of rare and pathogenic bacteria species from tick specimens such as Corynebacterium lactis (Lim et al, 2018) and P. lautus (Loong et al, 2018a). Even though no bacterial growth was observed for some tick specimens, we suggest that it was not due to the limitation of the agar culture media but the method employed for bacterial isolation (Stewart, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Visual inspection of the bacterial isolate after incubation in a 96-well plate at 37°C for 48 h [10] noted that the C. lipophiloflavum isolate did not produce biofilm. Morphological characteristics of the bacterium unveiled by transmission electron microscopy [11] displayed structures similar to C. phoceense [12] and C. lactis [13] [Figure . 2]. The bacterium showed characteristic clubshaped cell and the presence of an external lipid layer.…”
Section: Resultsmentioning
confidence: 99%
“…Although the C. lipophiloflavum isolate did not produce biofilm, it may switch from the dormant state to biofilm producer [17] on leaving the normal flora, as a result of selection and environmental pressures, further suggesting the undesirable influence of corynebacteria in dairy contamination. While C. lactis may seem harmless when it was first isolated from the cow's milk, recent studies have shown that it was also found in ticks and can cause infection in companion animals [13]. Hence, treating C. lipophiloflavum as a harmless normal flora of the cow could have disastrous aftermath to the entire dairy supply chain.…”
Section: Resultsmentioning
confidence: 99%
“…C. lactis and other Corynebacterium species are frequently found in raw milk (13, 30) and some isolates of Corynebacterium bovis and C. amycolatum are causative agents of mastitis in dairy cows (53, 54). C. lactis was eventually linked to infections in companion animals, but is not considered a pathogen so far and the determinants of infection remain unclear (55, 56). Interestingly, a putative BGC similar to corynaridin exists in the genome of an isolate of C. striatum from an intensive care unit (49).…”
Section: Discussionmentioning
confidence: 99%